2011
DOI: 10.1016/j.jhydrol.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Grid computing technology for hydrological applications

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. Advances in e-Infrastructure promise to revolutionize sensing systems and the way in which data are collected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 39 publications
(44 reference statements)
0
31
0
1
Order By: Relevance
“…Wehner et al (2008) suggested opportunities to address computational burdens, including hardware design (i.e., building enhanced computer processors for a specific application) and use of distributed and grid systems. A wide range of applications exists for grid and cloud computing systems (see Schwiegelshohn et al, 2010;Lecca et al, 2011;Fernández-Quiruelas et al, 2011). Improved computational power can also provide a basis to explore various model resolutions to identify critical scales for process representations (see Gentine et al, 2012) and to support computationally expensive offline calculations, such as groundwater processes, dynamic crop growth, river routing and model calibration (e.g., von Bloh et al, 2010;Rouholahnejad et al, 2012;Wu et al, 2013).…”
Section: Outstanding Challenges -Closing the Water Balance And Onlinementioning
confidence: 99%
“…Wehner et al (2008) suggested opportunities to address computational burdens, including hardware design (i.e., building enhanced computer processors for a specific application) and use of distributed and grid systems. A wide range of applications exists for grid and cloud computing systems (see Schwiegelshohn et al, 2010;Lecca et al, 2011;Fernández-Quiruelas et al, 2011). Improved computational power can also provide a basis to explore various model resolutions to identify critical scales for process representations (see Gentine et al, 2012) and to support computationally expensive offline calculations, such as groundwater processes, dynamic crop growth, river routing and model calibration (e.g., von Bloh et al, 2010;Rouholahnejad et al, 2012;Wu et al, 2013).…”
Section: Outstanding Challenges -Closing the Water Balance And Onlinementioning
confidence: 99%
“…Advances in distributed computing in conjunction with data availability from interoperable web services have made highresolution modeling of distributed hydrologic processes possible [40,41]. In the frame of enviroGRIDS, a highresolution SWAT (sub-catchment spatial and daily temporal resolution) model of the entire Black Sea catchment has been developed.…”
Section:  Swat_extractormentioning
confidence: 99%
“…A recent research paper [12] showed that the Grid technology is suitable for hydrology domain mainly for reducing the processing time. Different studies, such as in [13] and [14] prove that a Grid infrastructure, using efficient planning mechanisms, can lead to an increase of system performances.…”
Section: Hydrologic Modelsmentioning
confidence: 99%